Taxation of the Self‑employed in Poland and other EU Countries - a Comparative Analysis - Anna Krajewska; Piotr Krajewski (Comparative Economic Research. Central and Eastern Europe, 2021)
The article aims to compare the taxation of the self-employed in Poland and other EU countries. We show that, for years, Poland has been at the forefront of EU countries with the highest self-employment rates. Our analysis indicates that many people in Poland chose the status of self-employed, guided by tax optimization. Due to large differences in the burden of income tax and social security contributions of people working full-time and choosing self-employment, there are strong incentives to move from employment to fictitious self-employment. Our study shows that this significantly affects the revenues of the state budget and social security fund in Poland.
Keywords: E62; H24; J30; 330; self-employment; taxes; labor market; public finances